Preserving Artists’ Estates: A Professional Perspective. - Middleman, Rachel; Efimova, Alla (Art Journal)
An interview with Alla Efimova, the founder of the KunstWorks, a consulting firm for art is presented. Particular focus is given to her work helping artists and estates with legacy planning. Additional topics discussed include her the roles of executors of art estates, how she has clients in San Francisco, California, Los Angeles, California, and New York City, and the intersection of art and feminism.